Perancangan Video Dokumenter Nilai-Nilai Pencak Silat Bima Suci - Fadilah, Fadel Arthagena; Wantoro, Wantoro (Fakultas Desain Universitas Komputer Indonesia, 2021)
Bima Suci is a college of pencak silat located in Kuningan, West Java, which in every exercise instills spiritual and moral values for its pesilat. Communities in Kuningan regency lack information about this, hence the need for information facilities provided by the community so that information about the values in Bima Suci can be conveyed properly. Audio and visual information media in the form of documentary videos are media used to convey things in Bima Suci colleges because documentary videos can convey information and messages needed to the public more clearly.